Genome-wide dissection of the heat shock transcription factor family genes in Arachis - Wang, Pengfei; Song, Hui; Li, Changsheng; Li, Pengcheng; Li, Aiqin; Guan, Hongshan; Hou, Lei; Wang, Xingjun (Frontiers in Plant Science, 2017)
Heat shock transcription factors (Hsfs) are important transcription factors (TFs) in protecting plants from damages caused by various stresses. The released whole genome sequences of wild peanuts make it possible for genome-wide analysis of Hsfs in peanut. In this study, a total of 16 and 17 Hsf genes were identified from Arachis duranensis and A. ipaensis, respectively. We identified 16 orthologous Hsf gene pairs in both peanut species; however HsfXs was only identified from A. ipaensis. Orthologous pairs between two wild peanut species were highly syntenic. Based on phylogenetic relationship, peanut Hsfs were divided into groups A, B and C. Selection pressure analysis showed that group B Hsf genes mainly underwent positive selection and group A Hsfs were affected by purifying selection. Small scale segmental and tandem duplication may play important roles in the evolution of these genes. Cis-elements, such as ABRE, DRE and HSE, were found in the promoters of most Arachis Hsf genes. Five AdHsfs and two AiHsfs contained fungal elicitor responsive elements suggesting their involvement in response to fungi infection. These genes were differentially expressed in cultivated peanut under abiotic stress and Aspergillus flavus infection. AhHsf2 and AhHsf14 were significantly up-regulated after inoculation with A. flavus suggesting their possible role in fungal resistance.